The Manhattan Project - Hunt, Ken, 1991- (Brave & brilliant series ;, 2020)
"The hands of humans split the atom and reshaped the world. Gradually revealing a sublime nightmare that begins with spontaneous nuclear fission in the protozoic and ends with the omnicide of the human race, The Manhattan Project traces the military, cultural, and scientific history of the development of nuclear weapons and nuclear power through searing lyric, procedural, and visual poetry. Ken Hunt's poetry considers contemporary life--life in the nuclear age--broadly and deeply. It dances through the liminal zones between routine and disaster, between life and death, between creation and destruction. From the mundane to the extraordinary, Hunt's poems expose the depth to which the nuclear has impacted every aspect of the everyday, and question humanity's ability to avoid our destruction. Challenging the complicity of the scientists who created devastating weapons, exploring the espionage of the nuclear arms race, and exposing the role of human error in nuclear disaster, The Manhattan Project is a necropastoral exploration of the literal and figurative fallout of the nuclear age. These poems wail like a meltdown siren, condemning anthropocentric thinking for its self-destructive arrogance."--